Finite Volume Based Numerical Investigation On The Effects Of Internal Cooling And Film Cooling On The Thermal Performance Of Gas Turbine Blades - Shaker, Sufian Farid (2010)

(untitled)
The inlet temperature of modern gas turbine engines has been increased to achieve higher thermal efficiency and increased output. The blade surfaces including the leading edge, suction side and pressure side are exposed to the most extreme heat loads, and therefore, must be adequately cooled to maintain safety. This thesis presents steady computational predictions for a three-dimensional numerical investigation for different cooling arrangement of turbine blade model with both the internal cooling and combines cooling (film cooling) techniques.